Aspectos da relação interpessoal entre estagiários e professores da educação básica: uma análise dos discursos atitudinais de afeto em relatos de alunos- mestres. - Farias, Agenor Santos (Universidade Federal do Tocantins, 2022)
This research discusses the interpersonal relationship between trainees and Basic Education teachers, using as theoretical support the EVALUATION System from Halliday's Functional Systemic Linguistics (FSL), with the focus on the attitudinal discourses of affect in internship reports of the Language Arts Course. The way relationships develop in the school environment is of fundamental importance in the interaction between student-teacher and teacher, exerting influence on this dichotomy of practice-theory and theory-practice. The general objective is to analyze the aspects of the interpersonal relationship between trainees and Basic Education teachers, through the EVALUATION system. As for the specific objectives, we analyze the lexicon anchored in the evaluation system; discuss the relationship between the trainees and Basic Education teachers and identify in the textual productions of the trainees the discourse of affection. The research approach is qualitative, being supported by authors who address the theme of this research. The research is also documentary, as it uses a corpus consisting of 10 reports from Supervised Internship produced by undergraduate students of the Language Arts Course of the Federal University of Tocantins (UFT) Araguaína campus. These reports were processed in the IRAMUTEQ software and were also performed thorough scan by the researcher to locate discursive clippings that we call fragments. After analyzing the fragments grounded by Martin and White (2005) and Martin and Rose (2013) EVALUATION System, we found out that the way trainees were received by the Basic Education teachers in this phase of the Internship produced feelings of insecurity and unhappiness, which lead us to say that this first phase of Supervised Internship is sometimes uncomfortable for the trainees.